Critical analysis of medico-legal report writing by medical students - DS Bhullar; KK Aggarwal; Akash Deep Aggarwal; Deepak Kumar (GMC Patiala Journal of Research and Medical Education, 2019)
The present study was conducted to assess the level of medicolegal knowledge of the undergraduate medical students in writing medicolegal reports on crimes involving human body after completing their theory and practical course under syllabus and as a general overview after study and observation, it was concluded that in about twenty five percent of the students, their knowledge was not satisfactory and up to the desired levels which needs more exposure of the undergraduate medical students in examination of medicolegal cases in the interest of justice later on when actually put on duties as medico-legal experts.